Extending Mechanics to Minds The Mechanical Foundations of Psychology and Economics - Doyle, Jon (Cambridge University Press, 2013)
The ideas presented in this book draw on a broad range of fields, including mathematics, physics, philosophy, psychology, economics, politics, logic, and computation. The ideal reader of this book would bring to the reading a solid grasp of the foundations and development of mathematics, classical and relativistic rational mechanics, quantum theory, logic, probability, the theory of computation, psychology, artificial intelligence, and mathematical, psychological, and political economics